Mechatronic design of a modular artificial honeycomb for the automatic extraction of honey from apis melliferas bees in Huancayo, Peru. - Paitan Cardenas, Jose Alfredo (2024)
This research develops the mechatronic design of an artificial honeycomb for Apis Melliferas bees, which allows the automatic extraction of honey in the farms of the province of Huancayo, Peru, since Junin produces 208.26 tons of honey annually with traditional and obsolete techniques. This design was executed under the German VDI 2221 standard and contemplates the mechanical, electronic and control system, which are dimensioned according to the theories and laws of: distortion energy, polynomial 3 4 5, involute curve gears, Kirchhoff, Ohm, on-off control, among others. It was possible to design, in Inventor, the honeycomb structure whose cells have a 19° slope for the honey gravity flow, a gear-rack-gear system for the transmission of torque from the servomotor to the cam shaft to move the grid, which opens the flow duct; also, it was possible to design, in Proteus, the electronic system made up by the Arduino UNO, a servomotor of 2. 5 Kg-cm servomotor with rotation restricted to 110° and the 15mm force sensor; finally, the actuator control and the monitoring of the weight according to the on-off logic were programmed in Arduino IDE. According to the simulations performed, the design is technologically feasible.